MODERN INFORMATION TECHNOLOGY LAW AND DEMOCRATIC DISCOURSE - Mykulets, Vitalii (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2022)
Aim: distinction and systematization of the modern IT industry ideas and principles, which can be of use for the development of the national informational technology law, the one that will correspond with the democratic values of Ukrainian Constitution. For that purpose the analysis of the civil society phenomena was made, as well as the review of the materials dedicated to the IT industry advancements. Research methods: among others, the following were used: analytical method, generalization and systematic combined with complex approaches. Results: theoretical research made it clear that EU’s principles for IT growth are the guidelines for the development of the national informational technology law: 1) freedom of speech, including access to the variety of reliable information sources; 2) freedom of business creation and management within the Internet; 3) protection of the personal data and confidentiality, as well as the right to be forgotten; 4) protection of individual intellectual property on the Internet. Discussion: the analysis of the specialized literature as well as different normative acts showed that the progress of the civil society is connected to the dynamics and tempo of the information society development. Systematic and consequent formation of the civil society’s internet segment will provide more value to the democratic character of social relations. The described above situation affects the content and the development strategies of modern informational technology law as a complex law branch, which needs comprehension and awareness. Principles, which can be specified in the new policy in the ET-sphere and practice the number of denominations 1); 2) free and on-line service; 3) the number of links to the message, which can be used to increase the number of active and democratic numbers; 4) access to digital systems and services that are tolerant of standardized communications; 5; 6) ethical principles for algorithms, originating in the field; 7; 8) access to digital medical records.